Dynamics of Indonesia’s Competitiveness and Factors Affecting Coffee Exports in The China Market - Nindi Silvia Andriani; Dwi Rachmina; Anisa Dwi Utami (Jurnal Manajemen dan Agribisnis, 2025)
Background: As one of the world’s largest coffee exporters, Indonesia has significantly increased its coffee export value. The rapidly growing global coffee market, with China being one of the largest, shows a promising potential. Nonetheless, Indonesia is facing stiff competition from other coffee-exporting countries.Purpose: This study analyzes the dynamics of Indonesia's coffee competitiveness in the Chinese market and the factors affecting coffee exports to the Chinese market.Design/methodology/approach: This research uses RCA, EPD, X-Model and Gravity models as analytical tools. Findings/Results: The RCA analysis shows that Indonesia has a comparative advantage during the two research periods, while the EPD analysis finds that Indonesia has successfully improved its competitive position from lagging to rising in the second period. In addition, the X-Model analysis shows that China had a lower potential market for Indonesia in the first period. However, this market becomes optimistic in the next period, so there is much potential to continue increasing coffee exports to this country. In addition, gravity model analysis shows that factors such as the real GDP of exporting countries and China's real GDP affect coffee exports to the Chinese market.Conclusion: Indonesia's competitiveness has improved in the Chinese market, and the economic growth of exporters and China is essential in driving coffee exports to the Chinese market.Originality/value (state of the art): This study explicitly highlights China's fast-growing non-traditional coffee market, which currently shows high growth rates in coffee consumption. Keywords: coffee, EPD, gravity model, X-Model, international trade